Therapeutic efficacy of intra-articular injection of human adipose-derived mesenchymal stem cells in a sheep model of knee osteoarthritis - Jigang Lei; Xingyi Chen; Haohao Xie; Yuhao Dai; Zhongjin Chen; Liang Xu (Stem Cell Research & Therapy)
Abstract Background Mesenchymal stem cells have great potential for repairing articular cartilage and treating knee osteoarthritis (KOA). Nonetheless, little is known about the efficacy of human adipose-derived mesenchymal stem cells (haMSCs) for KOA in large animal models. Methods This study evaluated the therapeutic efficacy of haMSCs in knee articular cartilage repair in a sheep model of KOA. haMSCs were isolated, cultured, and characterized. KOA was surgically induced by anterior cruciate ligament transection and medial meniscectomy, followed by intra-articular injection of saline (negative control group) or haMSCs (haMSC group) into the right knee joint at 6 and 9 weeks after surgery. Sheep were sacrificed 21 weeks after surgery, and samples (whole knee joints, femoral condyles, and tibias) were collected, processed, and analyzed. Changes in knee articular cartilage were assessed by magnetic resonance imaging, micro-computed tomography, macroscopic analysis, histology, and immunohistochemistry. Results KOA caused the degeneration of the medial femoral condyle in the sheep model of KOA. Conversely, haMSCs repaired chondral defects and increased the thickness of knee articular cartilage. Conclusions These data suggest that the intra-articular injection of haMSCs can effectively repair articular cartilage defects in the knee.